2020
DOI: 10.3390/medicina56120713
|View full text |Cite
|
Sign up to set email alerts
|

Variant Anatomy and Its Terminology

Abstract: Variant anatomy, which is an integral part of anatomical science, is related to abnormalities in the human body structure. Our understanding of variant anatomy is based on thousand years of anatomical experience. These abnormalities generally do not interfere with the function of the human body and do not typically manifest as pathological nosological units. However, under certain conditions, these abnormalities can worsen existing pathological states or even evoke new ones. Understanding variant anatomy is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 91 publications
3
27
0
Order By: Relevance
“…14,15 different results by different studies suggest that there is influence of genetic variation, geographical distribution and race ethnicity on the position of appendix in various populations of the world. A study conducted in Canada by Hirpara et al and another study in Europe by Kachlík et al on the variations of anatomy of appendix reported similar findings as our study reported 16,17 .…”
Section: Discussionsupporting
confidence: 91%
“…14,15 different results by different studies suggest that there is influence of genetic variation, geographical distribution and race ethnicity on the position of appendix in various populations of the world. A study conducted in Canada by Hirpara et al and another study in Europe by Kachlík et al on the variations of anatomy of appendix reported similar findings as our study reported 16,17 .…”
Section: Discussionsupporting
confidence: 91%
“…Generally, anatomical variations are usually classified as frequent (10-100%), infrequent (1-10%), rare (<1%), and sporadic (<100 reported cases) in nature. 16 Based on the findings of this study, all ethmoid sinus anatomical variations may be considered as frequent findings among the Hong Kong or Southern Chinese population, with ANC being extremely frequent. This finding is clinically relevant in this population, especially for surgical procedures such as FESS, as inadequate removal of an ethmoid sinus variation such as ANC may result in iatrogenic chronic frontal sinusitis.…”
Section: Discussionmentioning
confidence: 63%
“…Prior knowledge of anatomical variants may have an importance in clinical practice, as it may be an unpleasant finding during a diagnostic or therapeutic procedure [21]. Radiologists and orthopedists could misinterpret the aperture as a lytic or cystic lesion, due to a relative radiolucency [1].…”
Section: Discussionmentioning
confidence: 99%